Corporate Social Responsibility (CSR) of MNCs in Bangladesh: A Study on Nestlé Bangladesh Limited - Ali , Md. Monsur (Global Disclosure of Economics and Business, 2018)
The article CSR of MNCs in Bangladesh scrutinizes how multinational companies conduct corporate social responsibility (CSR) in Bangladesh. The purpose of the study is to observe the framework of CSR areas and contribution to those areas by the Nestlé Bangladesh Limited. It considers the structure of CSR in the business of Bangladesh, which is now globally a vital issue for the development of society. It explains the systems of adopting CSR by the MNCs in Bangladesh, we can begin to see what implications arise from the fact that CSR is a financially developed nations’ concept. Developing country like Bangladesh is considered lagging behind in its understanding and adoption of CSR practices. Generally corporations do not expose their policies. This article tried to explore current practices of CSR by the leading MNC like Nestlé Bangladesh Limited which is operating its business activities proudly for the long since.